Sustainability assessment of continuous-flow hydrothermal synthesis of nanomaterials in the context of other production technologies. (20th December 2019) - Stieberova, Barbora; Zilka, Miroslav; Ticha, Marie; Freiberg, Frantisek; Caramazana-González, P.; McKechnie, Jon; Lester, Edward
Abstract: In this paper, we provide a comprehensive techno-economic and life cycle environmental evaluation of the continuous-flow hydrothermal synthesis (CFHS) of nanoparticles in the context of current production technologies. This method is compared with a set of competitor technologies: Plasma syntheses; Flame pyrolysis; Sol-gel synthesis; Batch Solvo/Hydrothermal syntheses; and Altair hydrochloride process. Technical criteria such as scale and variability of production and material properties are accounted for in the environmental and economic analyses. Case study nanomaterials are investigated with a range of potential applications: titanium dioxide (smart coatings, electronics, and water purification); zinc oxide (smart coatings, cosmetics); zirconium dioxide (nanocomposites, electronics); and lithium phosphate (lithium ion battery cathode material). Results: show that CFHS can be ranked among the most productive methods capable of producing up to 100–250 kg/h of different types of high quality NPs dispersed in water. In terms of the environmental impacts, this newly developed technology does not use any toxic solvents, there are no emissions into the environment and the risk of leakage of NPs into environment is negligible. Comparison of values of selected environmental impact categories Cumulative Energy Demand (CED) and Global Warming Potential (GWP) shows that CFHS can compete with industrial technologies with low production variability and limited product quality (e.g. sulfate and chloride processes) and achieves much better results in comparison with technologies with similar variability (e.g. HT plasma or sol-gel) and product quality (sol gel). The same conclusion can be made in the case of an economic assessment. The combination of large scale and variability of production and quality of produced NPs can be considered as the major source of competitive potential of CFHS. Graphical abstract: Image 1083 Highlights: We present a comprehensive comparison of nanoparticles production methods. Comprehensive comparison covers technical, environmental and economic aspects. Four nanoparticle types are included in the comparison: TiO2, ZnO, ZrO2, LiFePO4 . LCA was used as a key method for assessment of environmental impacts. Detailed cost structure of produced nanoparticles is revealed in this study.